Badanie w działaniu jako metoda badawcza w dydaktyce języków obcych - Wiśniewska, Danuta (Neofilolog, 2019)
The purpose of this article is to show how action research is used as a research method in foreign language didactics. Six articles have been chosen from refereed journals and analyzed in respect to such categories as research questions and problems, research aims, the relationship between research participants and researcher, research procedures, data collection methods, results and research quality. This initial analysis reveals that action research studies (1) do not easily fall into one distinct research paradigm, (2) can be both quantitative and qualitative, or mixed, (3) collaboration of research participants is often very limited, and (4) there are problems with quality criteria.